ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGN PADA PT. GUDANG GARAM TBK. PERIODE 2016 – 2020 - Fira R, Aldes Syah; Musyarofah, Ainun; Rahayu, Mundiyani (Perwira Journal of Economics & Business, 2022)
This research was conducted to analyze the financial performance of PT. Gudang Garam Tbk in the 2016-2020 period based on liquidity, solvency and profitability ratios. The research approach used is a quantitative approach. This research uses descriptive research. The subjects in this research were PT. Gudang Garam Tbk, while the object of this research is the annual financial report of PT. Gudang Garam Tbk. 2016-2020. The data analysis technique used is to calculate and analyze PT's financial reports. Gudang Garam Tbk in the 2016-2020 period using liquidity, solvency and profitability ratios. The company's financial performance is reviewed from the liquidity ratio as measured by PT's Current Ratio. Gudang Garam Tbk, is declared liquid, however the quick ratio (Quick Ratio) and cash ratio (Cash Ratio) are declared illiquid. Then the company's financial performance is reviewed from the solvency ratio as measured by DTAR and DTER, PT. Gudang Garam Tbk, was declared completely solvable. Meanwhile, if the company's financial performance is viewed from the perspective of profitability ratios as measured by ROA and ROE, PT. Gudang Garam Tbk, declared overall profit. This research is expected to provide data, information, references and an overview of the analysis of company financial performance in terms of liquidity ratios, solvency ratios and profitability at PT. Gudang Garm Tbk.